Assessment of heat generation and risk of thermal necrosis during bone burring by means of three-dimensional dynamic elastoplastic finite element modelling. (July 2020) - Chen, Yung-Chuan; Hsiao, Chih-Kun; Tu, Yuan-Kun; Tsai, Yi-Jung; Hsiao, An-Che; Lu, Chih-Wei; Yang, Chun-Yuh
Highlights: 3-D elastoplastic dynamic FE model can be effectively used for assessing the bone temperature distribution and the thermal affecting zone in bone during burring process. Frictional heat linearly increases with burring time. The risk zone of bone thermal necrosis is reduced as the feed rate increased and decreased as the rotation speed. ABSTRACT: During bone burring, the heat generated due to friction at the bone–burr interface may cause thermal damage to the bone. Therefore, it is necessary to assess bone temperature distribution around a burring site and identify high-risk regions for thermal necrosis due to bone burring. In this study, a three-dimensional (3-D) dynamic elastoplastic finite element model for the burring process was developed and experimentally validated to investigate the influence of burring parameters (rotational speeds: 3, 000, 10, 000, 15, 000 and 60, 000 rpm; feed rates: 0.5, 0.9, 1.5 and 3.0 mm/s) on heat generation and evaluate the risk region for thermal necrosis. Calculated bone temperatures were compared with experimental values and found to be in good agreement with them. The analytical results demonstrated a linear relationship between the burring time and friction energy. In addition, the friction energy increased with the bone temperature. The high-risk thermal necrosis zone was measured from the edge of burring (y-direction) at feed rates of 0.5, 0.9, 1.5 and 3.0 mm/s and was found to be 7.8, 7.3, 6.6 and 5.5 mm, respectively. When the burr rotational speed increased from 3, 000 to 60, 000 rpm, the high-risk zone for thermal necrosis increased from 4.5 to 8.1 mm. We concluded that both the friction energy and the bone temperature increased in proportion with the burr rotational speed. Reducing burr rotational speeds and/or increasing feed rates may decrease the rise in bone temperature, thus decreasing the potential for thermal necrosis near the burring site. Our model can be used to select the optimal surgery parameters to minimise the risk of thermal necrosis due to bone burring and to assist in the design of optimal orthopaedic drill handpieces.